Identification of Elementary Teachers’ Risk for Stress and Vocational Concerns Using the National Schools and Staffing Survey - Lambert, Richard G.; McCarthy, Christopher J.; Fitchett, Paul G.; Lineback, Sally; Reiser, Jenson (Education Policy Analysis Archives, 2015)
Transactional models of stress suggest that elementary teachers who appraise classroom demands as higher than classroom resources are more vulnerable to stress and likely to experience vocational concerns. Previous research using the Classroom Appraisal of Resources and Demands (CARD), a measure designed to assess teacher perceptions of classroom demands and resources, has supported transactional models with local samples. The current study replicated this previous research with two waves of large nationally representative data from the Schools and Staffing Survey (1999-2000 and 2007-2008). Theoretically-predicted differences were found, suggesting that an understanding of individual elementary teachers’ perceptions of demands and resources in the classroom could have important implications for policy and research aimed at addressing teachers’ vocational concerns.